2021
DOI: 10.1017/s1478951521000031
|View full text |Cite
|
Sign up to set email alerts
|

The psychological experience of pediatric oncology patients facing life-threatening situations: A systematic review with narrative synthesis

Abstract: Objective The purpose of this systematic review is to describe the elements of the psychological experience of pediatric oncology patients facing life-threatening situations and the corresponding care needs. Methods The study design is a systematic review following the PRISMA standard of qualitative, quantitative, and mixed-methods research. The review was conducted using multiple databases, including Scopus, Web of Science, PubMed, and PsycINFO. The risk of bias of the articles was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…New and advancing treatment options have significantly reduced the mortality rate of childhood cancer [ 3 ]. However, despite the improved chances of survival, as a life-threatening disease, cancer exposes children to potential losses, feelings of uncertainty about the disease, and a heightened sense of mortality and vulnerability [ 4 ]. All of these experiences trigger their exploration of personal value, meaning, and life goals throughout the illness trajectory, which, in turn, affects their spiritual well-being [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…New and advancing treatment options have significantly reduced the mortality rate of childhood cancer [ 3 ]. However, despite the improved chances of survival, as a life-threatening disease, cancer exposes children to potential losses, feelings of uncertainty about the disease, and a heightened sense of mortality and vulnerability [ 4 ]. All of these experiences trigger their exploration of personal value, meaning, and life goals throughout the illness trajectory, which, in turn, affects their spiritual well-being [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factores como el soporte social y familiar, la esperanza, encontrar un sentido en la vida y poder despedirse, contribuyen a la experiencia de sufrimiento (32) favoreciendo el bienestar emocional. Algunos de los elementos que la literatura identifica en relación sobre la experiencia psicológica de niños y adolescentes frente a situaciones de riesgo vital son los cambios en las relaciones, los pensamientos sobre la muerte, los cambios emocionales, los síntomas físicos que son fuente de sufrimiento, los cambios a nivel espiritual y los sentimientos de incertidumbre (33) . En la entrevista ESNA se evalúan 6 aspectos: I. Experiencia de Enfermedad; II.…”
Section: Discussionunclassified
“…It has been reported that the incidence and mortality rate of childhood cancer in China were 87.1 and 36.3 per million, respectively, after adjusting for age ( Zheng et al, 2015 ). Despite new and advanced treatment options that have improved survival rates, childhood cancer is still regarded as a life-threatening and stressful event ( Comas Carbonell et al, 2021 ). In addition to the physical suffering associated with cancer, the heightened sense of loss and threat of death cause childhood cancer patients to reflect and find meaning in relation to their diagnosis and its impact on their lives ( Holge-Hazelton et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%